Effects of termal treatment on the physical properties of Buchenavia sp. (branquilho) wood - Vollbrecht, Laysa Teles; Mascarenhas, Adriano Reis Prazeres; Melo, Rafael Rodolfo de; Lima, Maúcha Fernanda de Mota; Soteli, Ricardo Pereira; Pimenta, Alexandre Santos (Ambiente Construído, 2021)
This work aimed to evaluate the effect of heat treatment on the physical properties of wood from Buchenavia sp. The heat treatments were carried out at temperatures of 180 °C and 200 °C for 2 h. Apparent density (AD), basic density (BD), porosity (Ф), mass loss, longitudinal (LS), radial (RS), tangential (TS) and volumetric (VS) shrinkages and anisotropic factor (AF) were determined. The lowest values of basic density (0.67 g cm-3), apparent density (0.77 g cm-3), and porosity (43.3%) were observed for the wood treated at a temperature of 200 °C. Mass losses increased with increasing temperature and the highest values were observed under the condition of 200 °C (9.3%). The LS and AF was not affected by heat treatments. The mean values for RS (3.1%), TS (5.1%), and VS (9.1%) were reduced after the performance of heat treatments at temperatures of 180 °C and 200 °C, which did not differ from each other. The thermal treatments were able to reduce the dimensional instability of Buchenavia sp. Thermal treatments enhance the use of less prestigious Amazonian woods in the civil construction market.